Distance Learning Model Innovation for Early Childhood during COVID-19 Pandemic - Musyafa Ali; Samiaji, Mukhamad Hamid; Cesilia Prawening (Al-Athfal: Jurnal Pendidikan Anak, 2021)
Purpose – The COVID-19 pandemic has changed many lives, especially in the field of education. These changes start from the level of early childhood education, elementary education, to higher education. The learning process initially done conventionally in early childhood education has now been transformed into distance-learning or online. This sudden transformation of learning is essential to present an innovative distance learning model in the early childhood education environment. This study describes the distance learning model innovation for early childhood, implemented by PAUD Wadas Kelir, South Purwokerto, during the COVID-19 pandemic. Teachers designed this learning model at PAUD Wadas Kelir by combining fun and unique online and offline learning. Design/methods/approach – This type of research is field research with a descriptive qualitative method. In collecting data, researchers used three methods, i.e., observation, interviews, and documentation. The data analysis technique used, i.e., reducing data, presenting data, and drawing conclusions. Moreover, the validity of the data is tested using triangulation techniques. Findings – The results of this study show that there are ten learning model innovations implemented by ECE Wadas Kelir, i.e., learning with parental involvement, work projects, study visits, quizzes, online learning, creativity competitions, films and videos, creative and interactive stories, recording materials, and learning appreciation. Research implications/limitations – This case study focuses on Early Childhood Education (ECE) learning models applied to early childhood education institutions during the pandemic in PAUD Wadas Kelir, South Purwokerto, but it is unlikely that the situation is different elsewhere because the pandemic is Indonesia and global. Practical implications – This case study demonstrated how the application learning models of ECE during the pandemic are effective for children's growth and development. Originality/value – This paper contributes to knowledge and understanding of applying several learning models for ECE during the pandemic as reference material in implementing the learning process for early childhood. Paper type Case study